Mewujudkan Kecerdasan Naturalis Anak Usia Dini Melalui Peran Orang Tua - Nofrita Derit; Ismaniar, Ismaniar; Lili Dasa Putri (Journal Innovation In Education, 2025)
This article discusses the importance of the development of naturalist intelligence in early childhood as one aspect of Howard Gardner's theory of compound intelligence. Naturalist intelligence includes the ability of children to understand, appreciate, and interact with the natural environment. The active role of parents is a key factor in realizing this intelligence through daily activities, such as nature exploration, environmental education, and habituation of environmentally friendly behavior. The article analysis highlights practical strategies that parents can apply, including taking children for a walk in the park, observing flora and fauna, and discussing ecological issues in a simple way. The results of the study show that parental involvement not only increases children's naturalistic intelligence, but also forms a character of caring for the environment that supports the holistic development of early childhood. Thus, the development of naturalist intelligence through the role of parents can be an important foundation in instilling ecological values from an early age, while strengthening the dimension of character education that is oriented towards sustainability.